Body mass index and mortality in elderly men and women: the Tromso and HUNT studies - Kvamme, Jan-Magnus; Holmen, Jostein; Wilsgaard, Tom; Florholmen, Jon; Midthjell, Kristian; Jacobsen, Bjarne Koster (Journal of Epidemiology and Community Health, 2012)
The impact of body mass index (BMI; kg/m2) and waist circumference (WC) on mortality in elderly individuals is controversial and previous research has largely focused on obesity. With special attention to the lower BMI categories, associations between BMI and both total and cause-specific mortality were explored in 7604 men and 9107 women aged ≥65 years who participated in the Tromsø Study (1994–1995) or the North-Trøndelag Health Study (1995–1997). A Cox proportional hazards model adjusted for age, marital status, education and smoking was used to estimate HRs for mortality in different BMI categories using the BMI range of 25–27.5 as a reference. The impact of each 2.5 kg/m2 difference in BMI on mortality in individuals with BMI<25.0 and BMI≥25.0 was also explored. Furthermore, the relations between WC and mortality were assessed. We identified 7474 deaths during a mean follow-up of 9.3 years. The lowest mortality was found in the BMI range 25–29.9 and 25–32.4 in men and women, respectively. Mortality was increased in all BMI categories below 25 and was moderately increased in obese individuals. U-shaped relationships were also found between WC and total mortality. About 40% of the excess mortality in the lower BMI range in men was explained by mortality from respiratory diseases. BMI below 25 in elderly men and women was associated with increased mortality. A modest increase in mortality was found with increasing BMI among obese men and women. Overweight individuals (BMI 25–29.9) had the lowest mortality.